2013
DOI: 10.5566/ias.v32.p145-153
|View full text |Cite
|
Sign up to set email alerts
|

Stereological Evaluation of Brain Magnetic Resonance Images of Schizophrenic Patients

Abstract: Advances in neuroimaging have enabled studies of specific neuroanatomical abnormalities with relevance to schizophrenia. This study quantified structural alterations on brain magnetic resonance (MR) images of patients with schizophrenia. MR brain imaging was done on 88 control and 57 schizophrenic subjects and Dicom images were analyzed with ImageJ software. The brain volume was estimated with the planimetric stereological technique. The volume fraction of brain structures was also estimated. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…These patterns of preferentially altered extra-axonal environment are also consistent with reports of global increase in "free water" using the FWI technique in SZ cohorts 35 , although FWI conflates potential pathological mechanisms by defining a tissue compartment (intra-and extra-axonal) vs a free water (CSF) one. The pathological WM changes suggested by WMTI-W are indeed supported by neuroimaging findings beyond dMRI, such as a 14% reduction in WM volume 83 , and ultrastructural post-mortem studies reporting myelinated WM fiber pathology, such as decompacting and splitting of the myelin sheath, inclusions of vacuoles in-between myelin layers, small-axons atrophy, and the presence of swollen or dystrophic oligodendroglia [22][23][24] and microglia 25 . In parallel to these morphological changes, a 27-28% reduction in oligodendrocyte densities were reported in cortical layer III and subcortical areas 21 of SZ specimens.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These patterns of preferentially altered extra-axonal environment are also consistent with reports of global increase in "free water" using the FWI technique in SZ cohorts 35 , although FWI conflates potential pathological mechanisms by defining a tissue compartment (intra-and extra-axonal) vs a free water (CSF) one. The pathological WM changes suggested by WMTI-W are indeed supported by neuroimaging findings beyond dMRI, such as a 14% reduction in WM volume 83 , and ultrastructural post-mortem studies reporting myelinated WM fiber pathology, such as decompacting and splitting of the myelin sheath, inclusions of vacuoles in-between myelin layers, small-axons atrophy, and the presence of swollen or dystrophic oligodendroglia [22][23][24] and microglia 25 . In parallel to these morphological changes, a 27-28% reduction in oligodendrocyte densities were reported in cortical layer III and subcortical areas 21 of SZ specimens.…”
Section: Discussionmentioning
confidence: 54%
“…Pathological WM changes identified using WMTI-W are further supported by neuroimaging findings beyond dMRI, such as a 14% reduction in WM volume 94 , and ultrastructural post-mortem studies reporting myelinated WM fiber pathology, mainly consequence of the decompacting and splitting of the myelin sheath, but also the inclusions of vacuoles in between myelin layers, small-axons atrophy, and the presence of swollen or dystrophic oligodendroglia 2224 and microglia 25 . In parallel to these morphological changes, a 27-28% reduction in oligodendrocyte densities were reported in cortical layer III and subcortical areas 21 of SZ brains.…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, Elfaki et al (2013) reported that there is a statistically signi cant volumetric difference in the white matter of the brain in schizophrenia patients, and the white matter volumes of schizophrenia patients are lower in comparison to those of healthy individuals.…”
Section: Introductionmentioning
confidence: 91%